The Blind Forerunner, the Silent Visionary, and the Stone Guest: Hirt, Hegel, and Goethe imagining the "Nevermuseum" - Iannelli, Francesca (Revista Eletrônica Estudos Hegelianos, 2025)
The main aim of this paper is to reflect on the contribution offered by G.W.F. Hegel and J.W. Goethe to the musealization process that affected Germany in the late eighteenth and early nineteenth centuries. In order to do so, however, it will be essential to focus on an unjustly forgotten figure, such as that of Aloys Hirt (1759-1837), an uncomfortable and marginalized figure with whom both Hegel and Goethe were in contact, but who was also fundamental to the conception of the museum institution in Berlin. Hirt, in fact, stood on the threshold, poised between the eighteenth and nineteenth centuries, but was also between two giants of the age such as Hegel and Goethe, both of whom developed a rather original and evocative “museum” sensibility, which could be fruitfully recovered and brought into synergy with Hirt’s museum program to rethink the museal institution, helping to make real the “Nevermuseum”, that had yet to exist.
Keywords: Musealization; Aesthetics; Museum; Never-museum